(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
This study assessed the bacteriological quality of water source points for domestic use. The study was conducted at Mbarali District, which is found in the Mbeya region of Tanzania. Eight wards were selected for water sampling, which were Mawindi, Ubaruku, Rujewa, Chimala, Ihahi, Mapogoro, Igurusi, and Mahongole. The eight wards were chosen because their waters are highly polluted. All samples were properly sampled and transported the same day to the TARI Uyole Laboratory for chemical and biological analysis. In-situ physical parameters were tested in the field using multiparameter equipment. Using GIS software, a spatial bacteriological quality variation of domestic water source points was analyzed and presented. For testing Escherichia coli (E. coli), Total Coliform, and Total Heterotrophic Bacteria (THB), 60 samples of water were taken from 8 wards and put through a membrane filtration method. 75% of the water source points found to be less than 20 meters away from residential areas were observed to be associated with bacterial contamination. The mean concentrations of E. coli, total coliforms, and THB were 2.5 CFU/100 ml, 10.36 CFU/100 ml, and 70 CFU/100 ml, respectively. There was a significant difference between CFU of total coliforms in samples collected (p = 0.026). About 80% of the samples collected and analysed for water quality parameters did not conform to the TBS and WHO drinking water quality guideline value of no detection per 100 ml. The study concludes that domestic water point sources found in Mbarali District are located less than 20 meters away from residential areas, with significant unpaved areas and the presence of septic tanks and pit latrines that may lead to water pollution. Unsafe drinking water in Mbarali District is the primary route for waterborne disease transmission. Therefore, we recommend treating the water from dug wells and rivers/streams in Mbarali District before drinking it